Distribution of red cedar (Cedrela odorata L.) in the Hidalgo state, under current conditions and scenarios of climate change - Gómez Díaz, Jesús David; Monterroso Rivas, Alejandro Ismael; Tinoco Rueda, Juan Ángel (Instituto de Ecología, A.C., 2016)
The potential climatic areas for the distribution of red cedar (Cedrela odorata L.) were obtained in the state of Hidalgo under actual conditions, with meteorological information of 1961-1990 as base line, and under climate change conditions wich were obtained with two models: GFDL-R30 and HadCM3 for two time scenarios (2020 and 2050). The adjustment rates in temperature and rainfall obtained for each model were applied on climatic influence areas delimitated according to Gómez et al. (2006). Asoil moisture balance in the state’s surface was calculated under current and climate change conditions using the Thornthwaite, modified version III methodology (Monterroso and Gómez, 2003). The present percentage of the state surface with the vegetation types associated with red cedar is of 9,8% and the surface percentage estimated with some degree of suitability for this specie, using the climatic characteristics of the baseline scenario, is of 30,4%. The results of applied GFDL-R30 model shows an increment on the total surface with some degree of suitability with respect of the baseline scenario of 3,1% and 4,4% for the years 2020 and 2050, respectively, with a differential increment within the suitability classes. The surface estimated with some degree of suitability applying the HadCM3 model shows a decrement of 0,9% for the year 2020 and 0,2% for 2050. However, the class of Moderate suitable, change from 10,5% on the baseline scenario to 0% and 1,3% for the years 2020 and 2050, respectively, with almost all the areas in the lowest level of suitability.